A high-performance, solution-processable polymer/ceramic/ionic liquid electrolyte for room temperature solid-state Li metal batteries. (November 2021) - Lin, Xiujing; Chu, Chengcheng; Li, Zhuang; Zhang, Tingting; Chen, Jianyu; Liu, Ruiqing; Li, Pan; Li, Yi; Zhao, Jin; Huang, Zhendong; Feng, Xiaomiao; Xie, Yannan; et al.
Abstract: All-solid-state electrolytes provide a guarantee for the safe running of Li metal batteries (LMBs) with high energy density. Nevertheless, the low ionic conductivity and huge interfacial impedance between lithium anodes and electrolytes are the critical issues baffling their rapid development and practical application, particularly limiting their operation at room temperature. The introduction of ionic liquids (IL) is expected to solve the above problems. However, the effect of the IL-involved solid-state electrolytes on lithium dendrites suppression has not been clearly revealed and still necessitates in-depth evaluation. In this article, we report an in situ LiF-rich solid-electrolyte interphase (SEI) on the lithium anode triggered by reductive decomposition of IL and Li1.5 Al0.5 Ge1.5 (PO4 )3 -involved electrolyte. For the first time, the mechanism of SEI formed on Li metal based on IL-based solid-state electrolyte was unveiled. A combination of experimental and computational investigation manifests that the presence of Li1.5 Al0.5 Ge1.5 (PO4 )3 promotes the release of fluorine anion from IL, and a SEI layer with high content of LiF can be generated in situ through the reductive decomposition of wandering fluorine anion. Thanks to the high mechanical modulus from Li1.5 Al0.5 Ge1.5 (PO4 )3, the symmetric Li｜Li batteries equipped with synthesized solid-state composite electrolyte (SSCE) exhibit extremely stable Li plating/stripping behavior for more than 2700 h with a small polarization voltage of 50 mV at 0.1 mA cm −2 . Moreover, the assembled solid-state Li｜LiFePO4 batteries based on SSCE could operate steadily for 196 cycles at ambient temperature, with 90.7% capacity retention. These results provide a promising insight into the design of SSCE and realization of room temperature solid-state LMBs with high performance. Graphical Abstract: ga1 Highlights: Solid-state electrolyte based on ionic liquid/polymer/ceramic composites for room temperature solid-state LMBs is fabricated. The synergistic effect on the SEI formation with high content of LiF is unveiled by experimental and computational study. The high ionic conductivity and excellent mechanical strength of the SSCE enable superior cyclical stability.